(3TQM GdNQbis - (3TeS GdOjf CHh YHO Gddg eMeO Hf YHO Gddg Hf eMeO GdRQcTj GdeUQj, GdRQcTj,J (B772 (3g` s ((3eMeO Hf YeQ Hf eMeO Hf Ydi GdHYdi GdMfHdi s)
(3ChdgG (B:s
(3cJGH GdfcGM ai cdGe GdYQH GdhWA bGdg GdCRgQi s
(3BNQgG (B:s
(3fLR GdcJGH HbOQI GdYRjR GdhgGH s
(3GdcJGH GdeTQhM(B: (3eNJUQ GdNQbi dCHi GdbGSe YeQ Hf GdMSjf GdMfHdi J (B334 (3g`s
(3GdfSNI HgG MhGTs
(3GdfSNI ebGHdI Ydi fSNI bhHdJ Ydi fSNI GdeUfas
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdMfHdjs